Setting Aside Foreign Seated Arbitral Awards: Indian Supreme Court Introspects - Srinivasan, Badrinath; Rajiv, Roshni (Kathmandu School of Law Review, 2013)
This paper primarily provides a descriptive comment on the developments leading to the decision in BALCO from the passing of the 1996 Act and briefly analyses the effect of BALCO on arbitration in India. It provides a contextual background to the Indian Supreme Court’s decision in BALCO which has received wide acclamation in the international arbitration community. It discusses on the historical background of the 1996 (Indian) Arbitration and Reconciliation Act, the case regarding Bhatia International and developments subsequent to Bhatia International and proceeds towards a descriptive comment on BALCO and its effects on Indian arbitration.